Wordwall Labeled Diagram Gamification as a STEM-Based Social Sciences Learning Medium on Students' Critical Thinking Skills - Fauziyati, Khuldiana Azizah; Sriyanto, (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2025)
One of the skills that must be mastered by students in the 21st century to deal with problems and challenges in their personal and social life is critical thinking. Critical thinking skills can be improved through STEM (Science, Technology, Engineering, And Math) based wordwall labeled diagram gamification learning media. This study aims to determine the effect of wordwall labeled diagram gamification as a STEM-based IPS (Science, Technology, Engineering, And Math) learning medium on students' critical thinking skills. This study uses a quantitative approach to the type of pre-experimental research with a one group pretest–posttest design. The research was conducted on VA class students at State Elementary School 4 Kalibagor, Kalibagor District. The sample used was 21 students, namely 7 boys and 14 girls by purposive sampling. The instruments used are description questions based on indicators of critical thinking skills according to Ennis including elementary clarification, basic support, inference, advance clarification, and strategy and tactics. The critical thinking skills test was carried out in two stages, namely pretest and posttest. Based on the results, the average score for critical thinking skills in the pretest was 58.7% in the sufficient category, while in the posttest it was 81.2% in the very good category. The hypothesis test used was the paired sample t test, the results obtained through the IBM SPSS version 25 software with (0.05%) obtained a significance value (2-tailed) 0.000 <0.05. Based on this study, it can be concluded that H0 is rejected and H1 is accepted, so that there is an influence of wordwall labeled diagram gamification as STEM-based IPS (Science, Technology, Engineering, And Math) learning media on students' critical thinking skills.